A systematic literature review on SME financing: Trends and future directions. (4th May 2023) - Rao, Purnima; Kumar, Satish; Chavan, Meena; Lim, Weng Marc
ABSTRACT: Small and medium-sized enterprises (SMEs) are a significant source of employment for many people in developing and developed economies. However, one of the significant constraints that SMEs face is limited access to finance. Governments and financial institutions need to understand how SMEs access finance so that financial access for SMEs can be better promoted. In this vein, this paper conducts a systematic literature review to present a one-stop, state-of-the-art understanding of the extant literature on SME financing. The review encapsulates 280 papers from five top journals in the area of "small business management" between 1986 and 2020. The review is holistic as it explores the diversity of SME financing research and evaluates it in terms of publication trends (productivity, region), theoretical setup (theory building, application, elaboration, testing), methodological design (research design, data collection and analysis techniques), and themes (evolution, network). The paper concludes with proposals for future SME financing research.